2022
DOI: 10.3390/cancers14051354
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Paclitaxel Treatment for Patients with Pancreatic Ductal Adenocarcinoma with Peritoneal Dissemination Provides a Survival Benefit

Abstract: Background: Intraperitoneal chemotherapy using paclitaxel (i.p.-PTX) is expected to be a new therapeutic strategy for patients with pancreatic ductal adenocarcinoma (PDAC) and peritoneal dissemination. We evaluated the survival benefit of i.p.-PTX compared with standard systemic chemotherapy. Methods: Clinical data of 101 consecutive PDAC patients with peritoneal dissemination between 2007 and 2018 were analyzed. All patients were determined to have no other sites of distant organ metastasis to the lung, bone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
(59 reference statements)
2
10
0
Order By: Relevance
“…33 Moreover, the survival advantage of conversion surgery in patients with UR-PDAC with favorable responses to chemotherapy has been described in recent studies. 34 The present study also demonstrated better survival in patients who received preoperative chemotherapy for both Pb-and Pt-PDAC, and that the status of LN metastasis was significantly associated with OS even after preoperative therapy. Importantly, the incidence and extent of LN metastasis decreased in patients who received preoperative therapy for both Pb-and Pt-PDAC.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…33 Moreover, the survival advantage of conversion surgery in patients with UR-PDAC with favorable responses to chemotherapy has been described in recent studies. 34 The present study also demonstrated better survival in patients who received preoperative chemotherapy for both Pb-and Pt-PDAC, and that the status of LN metastasis was significantly associated with OS even after preoperative therapy. Importantly, the incidence and extent of LN metastasis decreased in patients who received preoperative therapy for both Pb-and Pt-PDAC.…”
Section: Discussionsupporting
confidence: 73%
“…Currently, Japanese guidelines recommend surgery after neoadjuvant chemotherapy for R/BR PDAC as a general rule 33 . Moreover, the survival advantage of conversion surgery in patients with UR‐PDAC with favorable responses to chemotherapy has been described in recent studies 34 . The present study also demonstrated better survival in patients who received preoperative chemotherapy for both Pb‐ and Pt‐PDAC, and that the status of LN metastasis was significantly associated with OS even after preoperative therapy.…”
Section: Discussionsupporting
confidence: 68%
“…In pancreatic cancer, the definition of peritoneal oligometastasis has rarely been discussed and established. Previous studies have found that conversion surgery and OS rates in peritoneal metastatic pancreatic cancer were unfavorable, with a prognosis ranged from 5.3 to 12.9 months (Table 2) [9,17,[20][21][22][23][24]. In contrast, Satoi et al [22] reported remarkable outcomes in patients with peritoneal metastasis treated with conversion surgery after a favorable response to intravenous and intraperitoneal paclitaxel with S-1.…”
Section: Surgery For Peritoneal Oligometastasismentioning
confidence: 98%
“… 46 , 47 Three reports were published on peritoneal mPDAC in 2021 and 2022 (Table 3 ). 16 , 48 , 49 Yamada et al reported a summary of two previous prospective studies on IP therapy for peritoneal mPDAC, focusing on conversion surgery. 48 Yamamoto et al 49 compared patients with IP treatment and conventional chemotherapy, of whom 12 underwent conversion surgery.…”
Section: Peritoneal Oligometastasismentioning
confidence: 99%